2006
DOI: 10.1128/iai.74.5.2619-2627.2006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Immunity Provides Protection against Pertussis in Newborn Piglets

Abstract: Pertussis continues to be a significant cause of morbidity and mortality in infants and young children worldwide. Methods to control the disease are based on vaccination with either whole-cell or acellular vaccines or treatment with antibiotics. However, despite worldwide vaccination infants are still at the highest risk for the disease. Here we used our newly developed newborn-piglet model to investigate whether transfer of maternal immunity can protect newborn piglets against infection with Bordetella pertus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 48 publications
(52 reference statements)
5
30
0
1
Order By: Relevance
“…In addition, colostrum was collected after farrowing and analyzed for the presence of B. pertussis-specific secretory IgA (S-IgA) and IgG antibodies by enzyme-linked immunosorbent assay (ELISA). In agreement with our previous reports (44), all vaccinated sows displayed high levels of both IgG and S-IgA antibodies (P Ͻ 0.003), whereas these antibodies were not detectable in colostrum from control sows (data not shown). Passive transfer of these antibodies to newborn piglets was demonstrated by analyzing the serum of piglets born either to vaccinated or nonvaccinated sows.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, colostrum was collected after farrowing and analyzed for the presence of B. pertussis-specific secretory IgA (S-IgA) and IgG antibodies by enzyme-linked immunosorbent assay (ELISA). In agreement with our previous reports (44), all vaccinated sows displayed high levels of both IgG and S-IgA antibodies (P Ͻ 0.003), whereas these antibodies were not detectable in colostrum from control sows (data not shown). Passive transfer of these antibodies to newborn piglets was demonstrated by analyzing the serum of piglets born either to vaccinated or nonvaccinated sows.…”
Section: Resultssupporting
confidence: 81%
“…pertussis antibodies in the serum of vaccinated sows, serum was collected prior to priming, boosting, and farrowing. As we have previously shown (44), high levels of both IgG and IgA isotypes were detected in the serum obtained from vaccinated sows prior to farrowing (P Ͻ 0.0001) but not in the serum from control sows (data not shown). In addition, colostrum was collected after farrowing and analyzed for the presence of B. pertussis-specific secretory IgA (S-IgA) and IgG antibodies by enzyme-linked immunosorbent assay (ELISA).…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…[1][2][3][4][5] Depending on species, animals use different approaches to transfer maternal antibodies. Maternal IgG is transferred mainly through the placenta before birth in guinea pigs, rabbits and humans, 6,7 whereas in ungulates such as sheep, cows and pigs, newborns receive maternal antibodies exclusively through colostrum.…”
Section: Introductionmentioning
confidence: 99%
“…20 It has been shown that SIgA protect infants and young children against gastrointestinal and respiratory pathogens, 18,19 such as Shigella, respiratory syncytial virus, and Bordetella pertussis. [21][22][23][24] However, little is known of the role, if any, of sIgA in contributing to protection of young infants from measles during the window of vulnerability when placentally transferred maternal antibodies are waning and prior to vaccination. There are few data on the prevalence of measles-specific antibodies in breast milk.…”
Section: Introductionmentioning
confidence: 99%